1632 Clinical predictors of fracture in patients with shoulder dislocation: systematic review of diagnostic test accuracy studies. Issue 12 (22nd November 2022) - Oldrini, Ilaria; Coventry, Laura; Novak, Alex; Gwilym, Steve; Metcalfe, David
Abstract : Aims, Objectives and Background: Pre-reduction radiographs are conventionally used to exclude important fracture before attempts to reduce a dislocated shoulder in the Emergency Department. However, this step increases cost, exposes patients to ionising radiation, and might delay closed reduction. Some studies have suggested that pre-reduction imaging may be omitted for a sub-group of patients with shoulder dislocations. The objective was to determine whether clinical predictors can identify patients that might safely undergo closed reduction of a dislocated shoulder without pre-reduction radiographs. Method and Design: A systematic review and meta-analysis of diagnostic test accuracy studies that have evaluated the ability of clinical features to identify concomitant fractures in patients with shoulder dislocation. All fractures were included except for Hill-Sachs lesions. Quality assessment was undertaken using the Quality Assessment of Diagnostic Accuracy Studies (QUADAS-2) tool. Data were pooled and meta-analysed by fitting univariate random effects and multi-level mixed effects logistic regression models. Results and Conclusion: Eight studies reported data on 2, 087 shoulder dislocations and 343 concomitant fractures. The prevalence of concomitant fracture was 17.5%. The most accurate clinical predictors were age >40 (LR+ 1.8 [95% CI 1.5–2.1]; LR- 0.4 [0.2–0.6]), female sex (LR+ 2.0 [1.6–2.4], LR- 0.7 [0.6–0.8]), first time dislocation (LR+ 1.7 [1.4–2.0]; LR-0.2 [0.1–0.5]), and presence of humeral ecchymosis (LR+ 3.0–5.7; LR- 0.8–1.1). The most important mechanisms of injury were: high-energy mechanism fall (LR+ 2.0–9.8), fall >1 flight of stairs (LR+ 3.8 [95% CI 0.6–13.1]; LR- 1.0 [95% CI 0.9–1.0]), and motor vehicle collision (LR+ 2.3 [0.5–4.0]; LR- 0.9 [0.9–1.0]). The Quebec Rule had a sensitivity of 92.2% (95% CI 54.6–99.2%) and specificity (33.3%, 23.1–45.3%) but the Fresno-Quebec rule maintained 100% sensitivity across three studies that included 564 shoulder dislocations and 98 fractures. In conclusion, the Fresno-Quebec Rule has undergone both internal and external validation and may now have a role in clinical practice.